PEMBENTUKAN KARAKTER RELIGIUS SISWA PADA MATA PELAJARAN AQIDAH AKHLAK MENGGUNAKAN MODEL PEMBELAJARAN DIRECT INTERACTION - Nanda Septiana (Universitas Islam Raden Rahmat Malang, 2022)
This study focuses on the formation of student religious character in the subjects of Aqidah Morals using a direct interaction learning model. This research method uses qualitative research with the type of classroom action research (CAR). The techniques used in the data collection procedure are interviews, tests, observations, and documentation. The results of this study indicate that in the first cycle, the percentage of students' completeness is 60%. This proves that there is an increase in the percentage of student learning mastery from 45% in the pre-cycle to 60% in the first cycle. However, the percentage of student learning mastery in the first cycle has not reached the target of 76%, so the research continues to cycle II with see important notes that still need to be reflected again for the next lesson. Constraints in the first cycle were corrected in the second cycle so that the learning mastery in the second cycle increased, indicated by the percentage of students' completeness in the second cycle reaching 85%. This shows that there was an increase of 45% from the pre-cycle to 60% in the first cycle and increased again to 85% in the second cycle. Based on the results of the research obtained by students in the pre-cycle, cycle I, and cycle II, it can be seen that the Direct Instruction Model can improve learning outcomes for Class IV students at MI Miftahul Hidayah Poreh Lenteng Sumenep for despicable and commendable behavior.